From Schmelt Camp to "Little Auschwitz" Blechhammer's role in the Holocaust - Barth, Susanne (Purdue University Press, 2025)
"From Schmelt Camp to "Little Auschwitz": Blechhammer's Role in the Holocaust is the first in-depth study of the second largest Auschwitz subcamp, Blechhammer (Blachownia Śląska), and its lesser known yet significant prehistory as a so-called Schmelt camp, a forced labor camp for Jews operating outside the concentration camp system. Drawing on previously untapped archival documents and a wide array of survivor testimonies, the book provides novel findings on Blechhammer's role in the Holocaust in Eastern Upper Silesia, a formerly Polish territory annexed to Nazi Germany in the fall of 1939, where 120,000 Jews lived. Established in the spring of 1942 to construct a synthetic fuel plant, the camp's abhorrent living conditions led to the death of thousands of young Jews conscripted from the ghettos or taken off deportation convoys from Western Europe. Blechhammer was not only used for selecting parts of the Jewish ghetto population for Auschwitz, but also for killing pregnant women and babies. As an Auschwitz satellite, Blechhammer became the scene of brutal executions and massacres of prisoners refusing to go on the Death March. This microhistory unearths the far-reaching complicity of often overlooked perpetrators, such as the industrialists, factory guards, policemen, and "ordinary" civilians in these atrocities, but more importantly, it focuses on the victims, reconstructing the prisoners' daily life and suffering, as well as their survival strategies." -- Publisher
"This volume is an abridged version of the thesis 'The Oberschlesische Hydrierwerke and the Auschwitz Subcamp Blechhammer, 1939-1945' (Oldenburg University, 2020).
Keywords: Geschichte 1939-1945; Judenvernichtung; Arbeitslager; Blachownia Śląska; Blechhammer (Concentration camp); Holocaust, Jewish (1939-1945); World War, 1939-1945 / Atrocities; Hochschulschrift